(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
In general, this study discusses the role of Petrus Kanisius Ojong as chief editor in Star Weekly magazine. His career which started as a journalist continued to grow and his position as editor-in-chief brought many changes. Star Weekly became a very popular Chinese magazine under Ojong’s leadership. This study aims to provide an understanding of the role and efforts of Petrus Kanisius Ojong in developing Star Weekly Magazine in Indonesia in 1951-1961. The research method used in this study uses historical methods which include heuristics, criticism, interpretation and historiography. Based on the research results, Star Weekly at the time headed by P.K. Ojong is growing rapidly due to several strategies, including publishing many interesting articles so that the magazine is read by many people from various circles. However, this magazine could not last long, because the contents of the magazine, both in the form of content and material written by Star Weekly, were considered contrary to the government, so that in the end Star Weekly was banned from publishing in Indonesia.